2020
DOI: 10.1177/2050313x20910920
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of remitting seronegative symmetrical synovitis with pitting edema: Case report and literature review

Abstract: Remitting seronegative symmetrical synovitis with pitting edema is a rare but well-recognized clinical entity that is easily overlooked due to lack of clinical vigilance. It is classically described as an acute onset of symmetrical tenosynovitis of both upper and lower extremities with pitting edema, mostly noted in elderly population. Young patients with other rheumatological diseases and unilateral involvement had also been reported, but symmetrical remitting seronegative symmetrical synovitis with pitting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…[ 1 ], but so far the pathological mechanisms remain poorly understood [ 2 5 ]. The main diagnostic elements for RS3PE are: (1) pitting edema of the hands and feet, (2) acute onset of polyarthritis, (3) age over 50 years, (4) negative serology for rheumatoid factor [ 3 , 5 , 8 ]. An association with positive human leukocyte antigen (HLA) B7 [ 1 , 3 5 ] or a high level of vascular endothelial growth factor (VEGF) was observed in several cases, but their role and diagnostic value are debated [ 2 4 , 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ], but so far the pathological mechanisms remain poorly understood [ 2 5 ]. The main diagnostic elements for RS3PE are: (1) pitting edema of the hands and feet, (2) acute onset of polyarthritis, (3) age over 50 years, (4) negative serology for rheumatoid factor [ 3 , 5 , 8 ]. An association with positive human leukocyte antigen (HLA) B7 [ 1 , 3 5 ] or a high level of vascular endothelial growth factor (VEGF) was observed in several cases, but their role and diagnostic value are debated [ 2 4 , 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infection-induced form seems to be related to parvovirus or Streptobacillus moniliformis infection [ 2 , 5 , 6 , 9 ]. RS3PE can also coexist with other autoimmune diseases, such as Sjögren’s syndrome, systemic lupus erythematosus (SLE), polyarteritis nodosa, or ankylosing spondylitis [ 3 , 4 ]. Concerning PMR, some authors suggested that RS3PE is a part of the same spectrum because their clinical presentation can overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiologically, there are no erosions. [10] Tenosynovitis has been demonstrated with the imaging of extremities using ultrasonography and /magnetic resonance imaging. In our cases, laboratory and radiological findings were consistent with those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other studies reported the presence of edema with delayed lymphatic drainage. 7 Classification criteria for RS3PE have not yet been established. Olive et al in 1997 proposed that all the following diagnostic criteria had to be satisfied in order to make a diagnosis of RS3PE: i) pitting edema in all 4 limbs; ii) acute onset; iii) age >50 years; and iv) negative RF.…”
Section: Introductionmentioning
confidence: 99%